Waterproof starch glue as well as preparation method and application thereof

By adding tackifying modified components and water-resistant agents during the preparation of starch glue, the bonding and water-repellent properties of starch glue are improved, and the problem of poor water-repellent properties in humid environments is solved, which significantly improves service life and stability.

CN119709046APending Publication Date: 2025-03-28浙江华信科技发展有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411756749.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing starch glue has poor waterproof performance in humid environments, resulting in a decrease in adhesion force and affecting the quality and service life of corrugated paper products.

Method used

The bonding and waterproofing properties of the starch glue are improved by adding tackifying modification components and waterproofing agents during the preparation of the starch glue. The viscosity-enhancing and modified components are prepared by click reaction and Schiff base reaction. The structure contains epoxy groups and ethers, which improves the density and bonding strength of the starch gel. The anti-water agent is prepared by phase transfer catalysis and acid binding agent reaction. The structure contains fluorine elements and long alkyl chains to form a superhydrophobic structure to prevent moisture from adhesion.

Benefits of technology

It significantly improves the waterproof and bonding properties of starch glue, extends its service life, avoids the problem of bond separation caused by moisture erosion, and ensures the stability and reliability of starch glue in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709046A_ABST
    Figure CN119709046A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of starch glue, and discloses waterproof starch glue as well as a preparation method and application thereof, the starch glue comprises the following raw materials: corn starch, water, a catalyst, an oxidizing agent, sodium hydroxide solid, sodium thiosulfate, borax, a tackifying modification component, a water repellent agent and a defoaming agent; wherein the tackifying and modifying component is an epoxy-terminated allyl polyether derivative containing a catechol structure, and after the tackifying and modifying component is mixed with the starch matrix, the adhesive property of the starch glue is effectively improved; the structure of the water-resistant agent contains a fluorine element with strong hydrophobicity, a silicon oxygen bond, a long alkyl chain and a tert-butyl chain link, so that the prepared starch glue has excellent waterproof performance, all the raw materials are matched with one another, the stability and reliability of the starch glue in a humid environment are ensured, and the service life of the starch glue is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of starch glue, and in particular to a waterproof starch glue and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous acceleration of my country's industrialization process, adhesives have become popular due to their stable chemical properties, simple production process, and fast curing speed. Among them, starch glue is made of starch as the base material, which has the advantages of good insulation, green environmental protection, and low price. It has important applications in corrugated paper, wood processing, fiberboard, plywood, etc.

[0003] In the corrugated paper bonding process, starch glue plays a vital role, and its performance is one of the key factors to ensure the quality of corrugated paper products. Since corrugated paper products will encounter various humid environments during transportation and storage, such as sea transportation, refrigerated storage or high-humidity warehouse environments, they are easily eroded by moisture. This requires starch glue to be able to maintain good performance in a humid environment, otherwise it will have a negative impact on the quality of corrugated paper products. However, studies have found that ordinary starch glue has poor waterproof performance. When it is in a humid environment for a long time, the bonding strength of the starch glue will decrease, and separation will occur at the bonding point, affecting the overall performance and service life of the corrugated paper products. In addition, the starch glue used for corrugated paper bonding needs to have excellent bonding properties to avoid problems such as material stratification or debonding due to insufficient bonding strength.

[0004] In the prior art, functional additives are often used to fill and modify the material matrix in order to improve the performance of starch glue. For example, the invention patent with the announcement number CN104926572B discloses a waterproof adhesive for ignition and a preparation method thereof. The adhesive uses starch as the main raw material and adds additives such as ethyl cellulose and waterproofing agent to make the prepared adhesive have good waterproof performance. Therefore, high-performance starch glue can be prepared by adding optimized components in a targeted manner during the preparation of starch glue. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a waterproof starch glue and a preparation method and application thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A waterproof starch glue comprises the following raw materials in parts by weight: 30-50 parts of corn starch, 150-250 parts of water, 0.1-0.3 parts of catalyst, 1-2 parts of oxidant, 2-3 parts of solid sodium hydroxide, 0.1-0.5 parts of sodium thiosulfate, 0.1-0.5 parts of borax, 5-7 parts of viscosity-increasing and modifying components, 6-9 parts of water repellent, and 0.1-0.3 parts of defoaming agent.

[0008] As a further solution of the present invention, the oxidant is hydrogen peroxide with a mass fraction of 20% to 40%.

[0009] As a further embodiment of the present invention, the preparation method of the viscosity-enhancing modified component comprises the following steps:

[0010] Step D1: Under nitrogen protection, epoxy-terminated allyl polyether is mixed with deionized water, stirred to form a uniform solution, and then mercaptoethylamine and a photoinitiator are added to the solution, mixed, and the system is placed under ultraviolet light for 3 to 7 hours to obtain an intermediate;

[0011] Step D2: Add the intermediate and N,N-dimethylformamide to a nitrogen-protected reactor, stir evenly, and then continue to add 3,4-dihydroxybenzaldehyde to the reactor. After the addition is completed, turn on the heating until the temperature in the reactor reaches 50-55°C. After keeping warm and stirring for 6-9 hours, remove the solvent by reduced pressure distillation to obtain a viscosity-enhancing modified component.

[0012] As a further embodiment of the present invention, in step D1, the photoinitiator is any one of benzoin isopropyl ether, benzoin ethyl ether or benzoin dimethyl ether.

[0013] As a further solution of the present invention, in step D1, the wavelength of the ultraviolet lamp is 365nm.

[0014] It can be inferred that the principle of the above scheme is: in step D1, the unsaturated olefinic functional group in the terminal epoxy allyl polyether structure can undergo a click reaction with the thiol group in the mercaptoethylamine structure under the irradiation of a photoinitiator and an ultraviolet lamp, thereby introducing an amino group into the structure of the terminal epoxy allyl polyether to obtain an intermediate; in step D2, the amino group can react with the aldehyde group, and the intermediate and 3,4-dihydroxybenzaldehyde are used as raw materials to undergo a Schiff base reaction with each other to obtain a viscosity-enhancing modified component.

[0015] As a further embodiment of the present invention, the preparation method of the water repellent comprises the following steps:

[0016] Step DD1: adding perfluoropolyether carboxylic acid to dimethyl sulfoxide, stirring to mix evenly, then adding tert-butyldimethylsilyl (R)-(-)-glycidyl ether and a phase transfer catalyst to the system, raising the system temperature to 70-80° C. under stirring conditions, and keeping the temperature for 4-8 hours, the whole process is carried out under nitrogen protection, and the material is cooled naturally, and then discharged to obtain a modified perfluoropolyether carboxylic acid;

[0017] Step DD2: Add the modified perfluoropolyether carboxylic acid to toluene and stir to form a uniform liquid. Add lauroyl chloride and an acid binding agent to the liquid under continuous nitrogen conditions. After the addition is completed, stir at room temperature for 4 to 6 hours, remove the nitrogen, and discharge the material to obtain a water repellent.

[0018] As a further embodiment of the present invention, in step DD1, the phase transfer catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate or benzyltriethylammonium chloride.

[0019] As a further embodiment of the present invention, in step DD2, the acid binding agent is any one of pyridine or triethylamine.

[0020] It can be inferred that the principle of the above scheme is: in step DD1, the carboxyl group in the perfluoropolyether carboxylic acid structure reacts with the epoxy group in the tert-butyldimethylsilyl (R)-(-)-glycidyl ether structure by catalysis through a phase transfer catalyst, thereby introducing a hydroxyl group into the structure of the perfluoropolyether carboxylic acid to obtain a modified perfluoropolyether carboxylic acid; in step DD2, the hydroxyl group in the modified perfluoropolyether carboxylic acid structure can react with the acyl chloride group in the lauroyl chloride structure under the action of an acid binding agent, thereby chemically connecting the lauroyl chloride to the structure of the perfluoropolyether carboxylic acid to obtain a water repellent.

[0021] A method for preparing waterproof starch glue comprises the following steps:

[0022] Step 1: Add corn starch and water to a reaction kettle, control the temperature in the kettle to 30-40°C, stir to form a uniform solution, then add the catalyst to the solution, mix well, continue to add the oxidant, react for 0.5-1.5h, use sodium hydroxide solution to adjust the pH value of the system to 9-10, and obtain oxidized starch;

[0023] Step 2: adding sodium hydroxide solid to the oxidized starch obtained in the first step, stirring for 25 to 35 minutes, and then adding sodium thiosulfate, stirring for 8 to 12 minutes to obtain a gelatinized starch slurry;

[0024] Step 3: Add the gelatinized starch slurry obtained in step 2, water, borax, and thickening and modifying components into a mixer, mechanically stir for 20 to 40 minutes, then add a water repellent and a defoaming agent, mix well, and obtain starch glue.

[0025] The invention discloses an application of waterproof starch glue, wherein the starch glue is applied to bonding corrugated paper.

[0026] Beneficial effects of the present invention:

[0027] (1) The thickening and modifying component prepared by the present invention is a terminal epoxy allyl polyether derivative containing a catechol structure in its structure. The large number of ether bonds and catechol structures contained in its structure make the prepared starch glue have excellent bonding properties, thereby avoiding the problems of material delamination or debonding of corrugated paper products due to insufficient bonding force when used for a long time. In addition, the epoxy groups contained in the structure of the thickening and modifying component can interact with groups such as carboxyl groups in oxidized starch, which is beneficial for the starch glue to show higher density, further enhance the bonding strength and waterproof performance of the starch glue, and greatly extend the service life of the starch glue.

[0028] (2) The present invention prepares a water repellent as a filling and modifying agent for starch glue. Since the structure of the water repellent contains highly hydrophobic fluorine elements, siloxane bonds, long alkyl chains and tert-butyl chain segments, the surface of the prepared starch glue produces a super-hydrophobic structure, which prevents the attachment of water and avoids the penetration phenomenon caused by long-term attachment of water. Therefore, it can cooperate with the thickening and modifying component to effectively improve the waterproof performance of the starch glue, avoid the starch glue being eroded by water, resulting in a decrease in adhesion and separation at the bonding point, and ensure the stability and reliability of the starch glue in a humid environment.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 This is an infrared spectrum test chart of the viscosity-enhancing modified component prepared by the present invention.

[0032] Figure 2 This is an infrared spectrum test diagram of the modified perfluoropolyether carboxylic acid and water repellent prepared by the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] Preparation of starch glue

[0036] Step 1: Add 30g corn starch and 60g water into a reaction kettle, control the temperature in the kettle to 30°C, stir to form a uniform solution, then add 0.1g catalyst into the solution, mix well, continue to add 1g hydrogen peroxide with a mass fraction of 20%, react for 0.5h, use a sodium hydroxide solution with a mass fraction of 10% to adjust the pH value of the system to 9, and obtain oxidized starch;

[0037] Step 2: Add 2 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 25 min, then add 0.1 g of sodium thiosulfate, stir for 8 min, to obtain a gelatinized starch slurry;

[0038] Step 3: Put the gelatinized starch slurry obtained in step 2, 90g water, 0.1g borax, and 5g thickening and modifying components into a mixer, mechanically stir for 20min, then add 6g water repellent and 0.1g tributyl phosphate, mix well, and obtain starch glue.

[0039] Example 2

[0040] Preparation of starch glue

[0041] Step 1: Add 40g corn starch and 70g water into a reaction kettle, control the temperature in the kettle to 35°C, stir to form a uniform solution, then add 0.2g catalyst into the solution, mix well, continue to add 1.6g hydrogen peroxide with a mass fraction of 25%, react for 1h, use a sodium hydroxide solution with a mass fraction of 10% to adjust the pH value of the system to 9.5, and obtain oxidized starch;

[0042] Step 2: Add 2.7 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 30 min, then add 0.3 g of sodium thiosulfate, stir for 10 min, to obtain a gelatinized starch slurry;

[0043] Step 3: Put the gelatinized starch slurry obtained in step 2, 130g water, 0.3g borax, and 6.5g thickening and modifying components into a mixer, mechanically stir for 30 minutes, and then add 8g water repellent and 0.2g tributyl phosphate to obtain starch glue.

[0044] Example 3

[0045] Preparation of starch glue

[0046] Step 1: Add 50g corn starch and 80g water into a reaction kettle, control the temperature in the kettle to 40°C, stir to form a uniform solution, then add 0.3g catalyst into the solution, mix well, continue to add 2g of 30% hydrogen peroxide by mass, react for 1.5h, use 10% sodium hydroxide solution by mass to adjust the pH value of the system to 10, and obtain oxidized starch;

[0047] Step 2: Add 3 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 35 min, then add 0.5 g of sodium thiosulfate, stir for 12 min, to obtain a gelatinized starch slurry;

[0048] Step 3: Put the gelatinized starch slurry obtained in step 2, 170g water, 0.5g borax, and 7g thickening and modifying component into a mixer, mechanically stir for 40min, and then add 9g water repellent and 0.3g tributyl phosphate to obtain starch glue.

[0049] Comparative Example 1

[0050] Preparation of starch glue

[0051] Step 1: Add 40g corn starch and 70g water into a reaction kettle, control the temperature in the kettle to 35°C, stir to form a uniform solution, then add 0.2g catalyst into the solution, mix well, continue to add 1.6g hydrogen peroxide with a mass fraction of 25%, react for 1h, use a sodium hydroxide solution with a mass fraction of 10% to adjust the pH value of the system to 9.5, and obtain oxidized starch;

[0052] Step 2: Add 2.7 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 30 min, then add 0.3 g of sodium thiosulfate, stir for 10 min, to obtain a gelatinized starch slurry;

[0053] Step 3: Put the gelatinized starch slurry obtained in step 2, 130g water, and 0.3g borax into a mixer, stir mechanically for 30min, and then add 8g water repellent and 0.2g tributyl phosphate to obtain starch glue.

[0054] Comparative Example 2

[0055] Preparation of starch glue

[0056] Step 1: Add 40g corn starch and 70g water into a reaction kettle, control the temperature in the kettle to 35°C, stir to form a uniform solution, then add 0.2g catalyst into the solution, mix well, continue to add 1.6g hydrogen peroxide with a mass fraction of 25%, react for 1h, use a sodium hydroxide solution with a mass fraction of 10% to adjust the pH value of the system to 9.5, and obtain oxidized starch;

[0057] Step 2: Add 2.7 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 30 min, then add 0.3 g of sodium thiosulfate, stir for 10 min, to obtain a gelatinized starch slurry;

[0058] Step 3: Put the gelatinized starch slurry obtained in step 2, 130g water, 0.3g borax, and 6.5g thickening modification component into a mixer, mechanically stir for 30 minutes, and then add 8g perfluoropolyether carboxylic acid and 0.2g tributyl phosphate to obtain starch glue.

[0059] Comparative Example 3

[0060] Preparation of starch glue

[0061] Step 1: Add 40g corn starch and 70g water into a reaction kettle, control the temperature in the kettle to 35°C, stir to form a uniform solution, then add 0.2g catalyst into the solution, mix well, continue to add 1.6g hydrogen peroxide with a mass fraction of 25%, react for 1h, use a sodium hydroxide solution with a mass fraction of 10% to adjust the pH value of the system to 9.5, and obtain oxidized starch;

[0062] Step 2: Add 2.7 g of sodium hydroxide solid to the oxidized starch obtained in the first step, stir for 30 min, then add 0.3 g of sodium thiosulfate, stir for 10 min, to obtain a gelatinized starch slurry;

[0063] Step 3: Put the gelatinized starch slurry obtained in step 2, 130g water, and 0.3g borax into a mixer, stir mechanically for 30min, and then add 8g dimethyl silicone oil and 0.2g tributyl phosphate to obtain starch glue.

[0064] The viscosity-enhancing modified components in the above examples and comparative examples were prepared by the following method:

[0065] Step D1: Under nitrogen protection, 5 g of terminal epoxy allyl polyether was mixed with deionized water, and after stirring to form a uniform solution, 1.2 g of mercaptoethylamine and 0.05 g of benzoin dimethyl ether were added to the solution, mixed well, and the system was irradiated under an ultraviolet lamp with a wavelength of 365 nm for 5 h, and the intermediate was obtained.

[0066] Step D2: Add 5 g of the intermediate and N,N-dimethylformamide to a nitrogen-protected reactor, stir evenly, and then continue to add 1.6 g of 3,4-dihydroxybenzaldehyde to the reactor. After the addition is completed, turn on the heating until the temperature in the reactor reaches 53°C. After keeping warm and stirring for 8 hours, remove the solvent by reduced pressure distillation to obtain a viscosity-enhancing modified component.

[0067] The infrared test of the viscosity-enhancing modified components was carried out using a FT IR-850 Fourier transform infrared spectrometer (Tianjin Gangdong Technology Development Co., Ltd.). Figure 1 As shown in the figure, the analysis shows that in the infrared spectrum of the viscosity-enhancing modified component, 830cm -1 With 1250cm -1 The absorption peak of epoxy group appears at 1195cm -1The absorption peak of CSC appears at 1680 cm -1 The absorption peak of C=N in Schiff base appears at 3020cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appears at 3290 cm -1 The absorption peak of hydroxyl group appears at 1035cm -1 The absorption peak of ether bond COC appears at

[0068] The water repellent in the above examples and comparative examples was prepared by the following method:

[0069] Step DD1: Add 5 g of perfluoropolyether carboxylic acid to dimethyl sulfoxide, start stirring to mix evenly, then add 1.0 g of tert-butyldimethylsilyl (R)-(-)-glycidyl ether and 0.05 g of tetrabutylammonium bromide to the system, raise the system temperature to 75° C. under stirring, and keep warm for 6 hours. The whole process is carried out under nitrogen protection, and the material is cooled naturally and discharged to obtain a modified perfluoropolyether carboxylic acid;

[0070] Step DD2: Add 5 g of modified perfluoropolyether carboxylic acid to toluene and stir to form a uniform liquid. Under continuous nitrogen conditions, add 1.6 g of lauroyl chloride and 0.1 g of pyridine to the liquid. After the addition is completed, stir at room temperature for 5 h, remove the nitrogen, and discharge the material to obtain a water repellent.

[0071] The modified perfluoropolyether carboxylic acid and water repellent were tested by infrared spectrometer FT IR-850 (Tianjin Gangdong Technology Development Co., Ltd.). Figure 2 As shown, analysis shows that in the infrared spectrum of modified perfluoropolyether carboxylic acid, 1238cm -1 The absorption peak of CF appears at 1035cm -1 The absorption peak of ether bond COC appears at 1750cm -1 The absorption peak of the ester group C=O appears at 3310 cm -1 The absorption peak of hydroxyl group appears at 1060cm -1 The absorption peak of Si-O appears at 1240cm -1 The absorption peak of CF appears at 1021 cm -1 The absorption peak of ether bond COC appears at 1759 cm -1 The absorption peak of the ester group C=O appears at 1051cm -1 The absorption peak of Si-O appears at the center, and the absorption peak of the hydroxyl group disappears.

[0072] Performance Testing

[0073] The starch glue prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 was uniformly coated on one side of the PET film, placed in an oven at 80°C for curing, and then cut into 10 cm×5 cm specifications and pasted on a standard steel plate to prepare a sample. The sample was subjected to a 180° peel strength test according to GB / T2792-2014 "Test Method for Peel Strength of Adhesive Tapes"; the sample was subjected to an initial adhesion test according to GB / T 4852-2002 "Test Method for Initial Adhesion of Pressure-Sensitive Adhesive Tapes (Rolling Ball Method)"; and the sample was subjected to a water contact angle test using a PZ-200SD contact angle tester. The specific test results are shown in Table 1:

[0074] Table 1 - Performance Test

[0075] Peel strength (N / 25mm) Initial viscosity(#) Water contact angle (°) Example 1 12.8 28 154 Example 2 13.5 30 156 Example 3 12.2 26 151 Comparative Example 1 10.4 18 150 Comparative Example 2 11.1 23 138 Comparative Example 3 8.5 11 125

[0076] It can be seen from the test results in Table 1 that the samples prepared in Examples 1 to 3 of the present invention have excellent waterproof performance and bonding performance; no viscosity-enhancing and modifying component is added to the sample prepared in Comparative Example 1, and the bonding performance of the sample is average compared with the example; perfluoropolyether carboxylic acid is used to replace the water-repellent in the sample prepared in Comparative Example 2, and the waterproof performance of the sample is not as good as that of the example, which may be because a superhydrophobic structure cannot be formed, resulting in a decrease in the waterproof performance of the sample; commercially available dimethyl silicone oil is used to replace the water-repellent in the sample prepared in Comparative Example 3, and no viscosity-enhancing and modifying component is added, so the various performances of the sample are poor.

[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A waterproof starch glue, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of corn starch, 150-250 parts of water, 0.1-0.3 parts of catalyst, 1-2 parts of oxidant, 2-3 parts of solid sodium hydroxide, 0.1-0.5 parts of sodium thiosulfate, 0.1-0.5 parts of borax, 5-7 parts of viscosity-enhancing and modifying components, 6-9 parts of water repellent and 0.1-0.3 parts of defoaming agent.

2. A waterproof starch glue according to claim 1, characterized in that, The oxidant is hydrogen peroxide with a mass fraction of 20% to 40%.

3. A waterproof starch glue according to claim 1, characterized in that, The preparation method of the viscosity-enhancing modified component comprises the following steps: Step D1: Under nitrogen protection, epoxy-terminated allyl polyether is mixed with deionized water, stirred to form a uniform solution, and then mercaptoethylamine and a photoinitiator are added to the solution, mixed, and the system is placed under ultraviolet light for 3 to 7 hours to obtain an intermediate; Step D2: Add the intermediate and N,N-dimethylformamide to a nitrogen-protected reactor, stir evenly, and then continue to add 3,4-dihydroxybenzaldehyde to the reactor. After the addition is completed, turn on the heating until the temperature in the reactor reaches 50-55°C. After keeping warm and stirring for 6-9 hours, remove the solvent by reduced pressure distillation to obtain a viscosity-enhancing modified component.

4. A waterproof starch glue according to claim 3, characterized in that, In step D1, the photoinitiator is any one of benzoin isopropyl ether, benzoin ethyl ether or benzoin dimethyl ether.

5. A waterproof starch glue according to claim 3, characterized in that, In step D1, the wavelength of the ultraviolet lamp is 365nm.

6. A waterproof starch glue according to claim 1, characterized in that, The preparation method of the water repellent comprises the following steps: Step DD1: adding perfluoropolyether carboxylic acid to dimethyl sulfoxide, stirring to mix evenly, then adding tert-butyldimethylsilyl (R)-(-)-glycidyl ether and a phase transfer catalyst to the system, raising the system temperature to 70-80° C. under stirring conditions, and keeping the temperature for 4-8 hours, the whole process is carried out under nitrogen protection, and the material is cooled naturally, and then discharged to obtain a modified perfluoropolyether carboxylic acid; Step DD2: Add the modified perfluoropolyether carboxylic acid to toluene and stir to form a uniform liquid. Add lauroyl chloride and an acid binding agent to the liquid under continuous nitrogen conditions. After the addition is completed, stir at room temperature for 4 to 6 hours, remove the nitrogen, and discharge the material to obtain a water repellent.

7. A waterproof starch glue according to claim 6, characterized in that: In step DD1, the phase transfer catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate or benzyltriethylammonium chloride.

8. A waterproof starch glue according to claim 6, characterized in that: In step DD2, the acid binding agent is any one of pyridine or triethylamine.

9. A method for preparing the waterproof starch glue according to claim 1, characterized in that: The following steps are involved: Step 1: Add corn starch and water to a reaction kettle, control the temperature in the kettle to 30-40°C, stir to form a uniform solution, then add the catalyst to the solution, mix well, continue to add the oxidant, react for 0.5-1.5h, use sodium hydroxide solution to adjust the pH value of the system to 9-10, and obtain oxidized starch; Step 2: adding sodium hydroxide solid to the oxidized starch obtained in the first step, stirring for 25 to 35 minutes, and then adding sodium thiosulfate, stirring for 8 to 12 minutes to obtain a gelatinized starch slurry; Step 3: Add the gelatinized starch slurry obtained in step 2, water, borax, and thickening and modifying components into a mixer, mechanically stir for 20 to 40 minutes, then add a water repellent and a defoaming agent, mix well, and obtain starch glue.

10. An application of the waterproof starch glue as claimed in claim 1, characterized in that: The starch glue is applied to corrugated paper bonding.

Citation Information

Patent Citations

  • A kind of waterproof adhesive for ignition agent and preparation method thereof

    CN104926572B